Penggunaan Serbuk Buah Pare (Momordicha charantia L) Terhadap Kematian Larva Aedes aegypti - Moelyaningrum, Anita Dewi; Shafarini, Anis Yulianti; Ellyke, Ellyke (HIGIENE: Jurnal Kesehatan Lingkungan, 2018)
Dengue Fever is a disease that has the higher patients in Indonesia. The disease caused by the dengue virus that transmitted by one of Aedes aegypti mosquito which usually sucks human blood. The aim of the research is to analyze the average difference of Aedes aegypti larvae death without treatment (0 g/L) and give the treatment (1.3 g/L, 1.5 g/L, 1.7 g/L). This is the True experimental research with Posttest only control design. The sample is 10 Aedes aegypti larvae instar III for each treatment so total totals 240 tail of larvae. The sampling technique is using simple random sampling because the populations are homogenous. Data were collected through by observation of larvae that died for 24 hours then analyzed using Kruskal Wallis test and continued with Post Hoc test with 5% significance level. The results showed that in the control group, the mortality of larvae at concentration 0 g/L and 1.3 g/L was not significant because p> 0,05 so statistically there was no difference of average death of Aedes aegypti larvae with the concentration. It is because of the low supply of Momordica charantia L powder. While the concentration of 1.5 g/L and 1.7 g/L based on statistic are significant because the value of p<0.05 so that there are differences in the average death of Aedes aegypti larvae. The factor that significant be the predictors of larvae mortality is a high of the powder and duration of observation. More pare powder are given and the length of the observation so the mortality rate of the larvae is higher. So the pare powder is statistically effective start on a concentration of 1.5 g/L and 1.7 g/L with an observation time of 12 hours and 24 hours. Keywords: Concentration, time, Momordica charantia L.